Anxiolytic, Antidepressant, and Anticholinesterase Effects of Essential Oil from Myrcia sylvatica (G.Mey.) DC - Antônio Quaresma da Silva Júnior; Mariana Maciel Garcia; Wanderson da Silva Farias; Deise Juliane dos Anjos de Sousa; Adenilson de Sousa Barroso; Pablo Luis Baia Figueiredo; Gabriela B. dos Santos; Ricardo Bezerra de Oliveira; Rosa Helena Veras Mourão (Biomolecules)
Aromatic plants are rich sources of essential oils (EOs), recognized for their therapeutic properties due to their diversity of phytochemicals. This study investigated the anxiolytic and antidepressant effects of Myrcia sylvatica essential oil (MsEO) through inhalation in an animal model and its in vitro anticholinesterase (AChE) activity. The EO was obtained by hydrodistillation, and its volatile constituents were analyzed by GC-MS. Swiss mice were exposed to doses of 0.1%, 1%, and 2% of the EO via an inhalation apparatus. The anxiolytic activity was assessed using the elevated plus maze and light–dark box tests, while antidepressant activity was evaluated using the tail suspension and forced swimming tests. To examine potential side effects, the animals were subjected to rotarod, Y-maze, and Morris water maze tests to assess motor coordination, memory, and learning. Anticholinesterase activity was determined by direct bioautography and colorimetry based on the Ellman method. The results demonstrated that inhalation of MsEO at doses of 0.1% and 1% significantly reduced anxiety and depressive-like behaviors without impairing memory, learning, or motor coordination in the animals. Moreover, MsEO inhibited acetylcholinesterase with an IC50 of 0.47 μg/mL. These findings suggest that MsEO has potential therapeutic applications for anxiety and depression disorders, with additional anticholinesterase activity warranting further investigation in cognitive-related conditions.